Assessment of nutritional status in relation to socio economic determinants among Sabar tribes of Jhargram district of West Bengal, India - Mandal, Anindita; Roy, Debasmita (International Journal Of Community Medicine And Public Health, 2022)
Background: This cross-sectional study was undertaken to assess the nutritional status in relation to socio-economic determinants among sabar tribes of Jhargram district, West Bengal. Methods: Nutritional status of 169 children, adolescent and adult male and female tribal people was taken to measure body height, body weight and BMI. Socio economic status including family income, occupation, family size, educational status, source of drinking water, use of sanitary latrine, smoking habit and prevalence of diseases among sabar tribal people was recorded by questionnaire study. Results: Undernutrition is prominent among sabar children and adolescent. The people of this area were relatively underprivileged to access to safe drinking water and sanitary latrine. The health status of sabar people of this locality was associated strongly with family income and educational status. Although other factors like safe drinking water ,use of sanitary latrine, occupation , no of children in a family, smoking habit showed insignificant association. Besides, occupation and life style related diseases were very common among adult sabars. Conclusions: Percentage of undernourished people especially children and adolescent in this study is large, they required a variety of interventions to improve quality of life like- assessment of nutritional status, causes of nutritional deficiencies and imbalance, formulation of diet plan and its implementation where required.